Prioritizing Mental Health: A Cross-Sectional Investigation of Depression Prevalence and Risk Factors among Medical Students in Peshawar, Pakistan - Nida Gul; Ayaz Ali; Rizwanullah; Khayam; Manahil Saeed Khan; Faiza Gul; Aiysha Gul; Shehriyar; Kashif Ali; Syed Owais Haseeb (International Journal of Medical Students, 2024)
Background: Depression is a significant problem among medical students worldwide, affecting their well-being and potentially compromising patient care. This study aimed to determine the prevalence of depression among medical students in Peshawar, Pakistan, and to identify the associated risk factors. Methods: A cross-sectional study was conducted from April to June 2023, involving medical students from seven colleges in Peshawar. We employed stratified sampling to distribute surveys to students. We collected data on socio-demographic characteristics, prevalence of depression using the Hospital Anxiety and Depression Scale (HADS), and depression risk factors. We used multivariate logistic regression, clustered by university, to assess factors associated with depression. Results: Out of 400 distributed questionnaires, 324 were returned (response rate: 81%). The participants' mean age was 21.70 ± 1.65 years, with 53.1% being females. The prevalence of depression was 19.4% and 26.2% were borderline cases. No variables were found to be significantly linked to depression in our multivariate regression model. However, male gender, year of study, experiencing discrimination or harassment in medical school, and having negative perceptions of medical school's impact on mental health had odds ratios above 1, with confidence intervals including the null value. Conclusion: This study reveals a high prevalence of depression among medical students in Peshawar, Pakistan. It emphasizes the need to address risk factors and establish support systems to minimize the impact of depression on students' well-being and academic performance. Further studies are necessary to identify modifiable factors associated with depression in medical students.